2021
DOI: 10.1093/cercor/bhab161
|View full text |Cite
|
Sign up to set email alerts
|

White and Gray Matter Abnormalities in Australian Footballers With a History of Sports-Related Concussion: An MRI Study

Abstract: Sports-related concussion (SRC) is a form of mild traumatic brain injury that has been linked to long-term neurological abnormalities. Australian rules football is a collision sport with wide national participation and is growing in popularity worldwide. However, the chronic neurological consequences of SRC in Australian footballers remain poorly understood. This study investigated the presence of brain abnormalities in Australian footballers with a history of sports-related concussion (HoC) using multimodal M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The rCFL players had a BDI-II score of 8.15 ± 7.03, which was significantly higher (p = 0.0021) compared to healthy age/sex matched controls (2.2 ± 2.68). The rCFL group mean score of 8.15 fell within the none to minimal depression category (0-13), with only some rCFL players scoring mild depression (10)(11)(12)(13)(14)(15)(16)(17)(18). But on average, the rCFL population reported almost 4 times greater levels of depressionlike symptoms than controls.…”
Section: Clinical Testing Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The rCFL players had a BDI-II score of 8.15 ± 7.03, which was significantly higher (p = 0.0021) compared to healthy age/sex matched controls (2.2 ± 2.68). The rCFL group mean score of 8.15 fell within the none to minimal depression category (0-13), with only some rCFL players scoring mild depression (10)(11)(12)(13)(14)(15)(16)(17)(18). But on average, the rCFL population reported almost 4 times greater levels of depressionlike symptoms than controls.…”
Section: Clinical Testing Resultsmentioning
confidence: 92%
“…12 Extensive research has been focused on the neuroimaging-based assessment of subjects in the acute (hours to days) and sub-acute (days to weeks) periods post-concussion. [12][13][14] Studies have shown that participation in collision sports can lead to widespread grey and white matter abnormalities, 15,16 however, neuroimaging research into the chronic effects of a history of concussion in older adults has produced variable and potentially contradictory results. For example, Terry et al (2019) found only minimal white matter damage in the internal capsule in former high school football players with a history of at least two concussions, now aged between 40 to 65, 17 compared to Guell et al (2020) who found widespread functional connectivity dysfunction in the cerebrum and cerebellum in aging, retired athletes 18 or Clark et al (2018) who found white and grey matter alterations that were associated with number of concussions and career length in former collegiate athletes.…”
Section: Introductionmentioning
confidence: 99%
“…A questionnaire was administered pertaining to factors including demographics (ie, age, gender, height, weight), sporting history (ie, sports played, age they commenced collision sports, age they commenced all sport, years participating in collision sport, years participating in all sports), years of education and history of concussion (number and dates of previous concussions). 4 , 24 - 29 The ‘sport concussion assessment tool’ (SCAT; SCAT3 for 2017/18 players, SCAT5 for 2019 players) assessed symptom severity (maximum 132) at 2-, 6- and 13-days after SRC.…”
Section: Methodsmentioning
confidence: 99%
“…A number of promising biomarkers have been developed with the aim of objectively determining recovery. Magnetic resonance imaging (MRI) techniques including magnetic resonance spectroscopy [ 4 ] and diffusion weighted imaging [ 5 8 ] have been used to investigate a range of often subtle physiological cascades that follow SRC. Quantitative susceptibility mapping (QSM) is a comparatively new technique that utilizes MR phase images to map tissue susceptibility ( χ ) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%